Belastungsreduzierende Bandensysteme im Eishockey: Experimentelle Untersuchung zur Performance - Schmitt, K. U.; Muser, M.; Thüler, H.; Brügger, O. (bfu-Report, 76, 2017)
Impact testing of different dasher board systems in ice hockey Ice hockey is a sport with a high risk of injury. Male athletes have the highest incidence rate, with injuries to the lower extremities (especially knees) and to the upper extremities (shoulder) being the most common. In addition, a lot of publicity is given to brain injuries suffered because they can lead to long-term consequences. Frequent injury mechanisms are collisions between two players, a player falling on the ice or a player crashing into the dasher board. Dasher boards surround the ice-hockey rink. While certain characteristics of the boards are specified by corresponding standards, there are currently no concrete specifications as to what a board system must actually do in order to limit the risk of injury as far as possible. This project investigated whether ice-hockey boards of a new design reduce the biomechanical load on a player on impact. The exact performance of different ice-hockey boards was analysed in tests using a dynamic pendulum as well as in tests with crash test dummies. It turned out that a new board system design offers greater flexibility than previous systems. The boards are deflected further on impact, but their effective mass - in relation to the mass of a player - remains high especially in the event of head impact. Accordingly, while a player`s biomechanical loads are reduced by all the new systems, injuries caused by the impact with the perimeter boards can still be expected in future due to the mass difference. The tests also showed that the system with the highest deflection is not necessarily the system that leads to the lowest biomechanical load. There is no linear correlation between deflection and biomechanical load. In summary, the new dasher board system design can be given a fundamentally positive assessment. There are no recognizable disadvantages, but the advantages do not seem to be exhausted yet. Further development of the perimeter board systems should be the goal in order to further reduce the loads on the players.